Learning Management System Migration: An Analysis of Stakeholder Perspectives - Ryan, Thomas G; Toye, Mary; Charron, Kyle; Park, Gavin (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2012)
In this mixed methods study the authors describe the institution-level perceptions of stakeholders transitioning to a new learning management system (LMS). We address issues related to change, the institution’s administration of the transition process, problems encountered, and realized learning via online survey data collection, analysis, and interpretation. We further detail results of a faculty survey, which sought to illuminate the LMS transition experience. The summation includes suggestions for institutions as they prepare for, and move through, foreseeable LMS change and transition.